The RNA-seq based endometrial receptivity test (rsERT) compared to pinopode: A better diagnostic tool for endometrial receptivity for patients with recurrent implantation failure in Chinese population - Chen, Jingjing; He, Aihua; Zhang, Qiong; Zhao, Jing; Fu, Jing; Li, Hui; Li, Yanping (Frontiers in Endocrinology, 2022)
Displaced window of implantation (WOI) is one of the endometrial origins that accounts for implantation failure, especially for patients with recurrent implantation failure (RIF), yet no standard diagnostic tool has been recognized. The study consists of two parts, aiming to compare the concordance and efficacy of the diagnostic tools, the newly developed RNA-seq based endometrial receptivity test (rsERT) to the conventional pinopode, in diagnosing WOI and guiding personalized embryo transfer (pET). With the same group of RIF patients, the rsERT diagnosed 32 patients (65.31%) with normal WOIs, and most of the displacements were advancements (30.61%). While according to pinopode, only 14 patients (28.57%) were found with normal WOIs, and most patients (63.27%) presented delayed growth patterns. After conducting pET, patients in the rsERT group had higher successful pregnancy rates while requiring fewer ET cycles (50.00% vs. 16.67%, p=0.001). The study proved poor consistency between the diagnostic tools of endometrial receptivity based on cellular structure and gene profiling, and it supported rsERT as a reliable tool with potential clinical value.